Automatic Packaging Conveyor Tracking System Based on Arduino Uno Using Photodiodes and SRF04 Ultrasonic Sensors - Rachmanda Aisah Putri; Nur Kholis; Farid Baskoro (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
Tracking Conveyor in this packaging is a system whose mechanics work to move an item that is on the conveyor from one place to another, basically this conveyor is widely used in the industrial world which is used for the transportation of very large goods. In order to achieve a large number of products to be produced, a fairly good and efficient movement is needed in order to achieve the production target, at this time there is still a lot that is still relatively manual carried out by human labor, while the movement to move goods quickly requires tools to move products to other places. in the box. This study aims to produce a conveyor tracking system in automatic packaging based on AU (Arduino Uno) using an ultrasonic sensor SRF04 and a photodiode sensor. The method used is a quantitative type method, which is a research method that uses numerical values, this type of research has many approaches that use numerical values, ranging from data collection and display of research results. With the above shortcomings, the authors encourage research and development of the use of appropriate and efficient technology, by combining ultrasonic sensors and photodiode sensors with conveyors. The result of this research is the sensor combination with the addition of a photodiode sensor combination to detect the presence of objects that have been applied to run the conveyor. In running this conveyor, two sensor requirements must be met, namely the distance to the object with the ultrasonic sensor should not be less than 5 cm and not more than 11 cm. The second requirement is that the distance between the object and the photodiode sensor should not be more than 11 cm. If both conditions are met, the conveyor will run.